SEDF: a spoofed email detection framework employed by a lightweight web browser plug-in for detecting the spoofed email / Al Ya@Geogiana Buja...[et al.] - Buja, Al Ya@Geogiana; Ahmad, Illiasaak; Zolkeply, Mohd Syafiq (2014)
E-mail spoofing is the one of the greatest thread among the computer user especially for those person or organization which always use an e-mail as a main medium to communicate. This fraud can affect the user and organization credential and lead to a serious problem information leak and so on. Most of the victims that involved in this case is an IT illiterate user who literally does not have enough knowledge to differentiate between the fake emails. There are sort of protection or mechanism that have been developed to help user but their complicated brings inconvenient and difficulties to the user. In this project, it introduce to a mechanism to detect an e-mail. The main idea is to identify an e-mail that user feel suspicious about the content and originality. The method used to detect fake e-mail is by tracing back the email header. Any email that sent out still have several stored in the mail header. Therefore, this research will propose the SEDF to overcome the problem of email spoofing. The algorithm use to match the word in the searching period in the mail header is based on The Boyer-Moore. Boyer - Moore algorithm was claimed to be the fastest algorithm among the others. Using this approached, it is guarantee that it is able to help user to identify fake mail.